“Estrategias virtuales que permitan el aprendizaje efectivo de las ciencias sociales en los estudiantes de 4to año de educación general básica paralelo “A” de la Unidad Educativa “10 de Enero” del cantón san Miguel 2021-2022” - Sanchez Cuji, Bryan Sabino (2022)
According to the investigation, it is established that this has meant a social problem, so it is necessary to analyze the different approaches of what digital citizenship represents, which is why inconsistencies have been evidenced around web management. The responsible use of the mechanisms and tools, brought by the Ministry of Education, by virtue of the flow of information, in this sense it is vital to attend to this issue since this is developed in the light of ignorance and lack of importance for him learning and teaching of an optimal digital language that allows establishing virtual strategies to improve social science classes, important for their development and good management. That is why it is necessary to address this problem, establishing causes and effects by virtue of technological actions, which are carried out based on traditional order planning. Based on this, it is evident that this is a current problem that has been generated by the level of training of digital environments, therefore, this has sparked controversy, which is why it is important to educate 4th grade EGB students, the U.E. "JANUARY 10", with social responsibility.